2009
DOI: 10.1111/j.1469-8137.2009.03007.x
|View full text |Cite|
|
Sign up to set email alerts
|

Tree endurance on the Tibetan Plateau marks the world’s highest known tree line of the Last Glacial Maximum

Abstract: Because of heterogeneous topographies, high-mountain areas could harbor a significant pool of cryptic forest refugia (glacial microrefugia unrecognized by palaeodata), which, as a result of poor accessibility, have been largely overlooked. The juniper forests of the southern Tibetan Plateau, with one of the highest tree lines worldwide, are ideal for assessing the potential of high-mountain areas to harbor glacial refugia. Genetic evidence for Last Glacial Maximum (LGM) endurance of these microrefugia is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
165
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(185 citation statements)
references
References 73 publications
15
165
2
3
Order By: Relevance
“…40-43) support the idea that refugia occurred along the southeastern margin of the QTP as well as in areas further west and north, even at high elevation (e.g., refs. [44][45][46]. This aligns with geological evidence that ice-free areas were present across the QTP and adjacent mountains throughout the Quaternary (47).…”
Section: Discussionsupporting
confidence: 68%
“…40-43) support the idea that refugia occurred along the southeastern margin of the QTP as well as in areas further west and north, even at high elevation (e.g., refs. [44][45][46]. This aligns with geological evidence that ice-free areas were present across the QTP and adjacent mountains throughout the Quaternary (47).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, based on mismatch distribution analysis and neutrality tests, we found no evidence of long-distance dispersal or population expansion. As some other ancient and drought-resistant species in southwest China (Opgenoorth et al 2010;Wang et al 2010), C. debaoensis may have been able to endure cold conditions during the glacial periods and may have remained in multiple microrefugia throughout its current range. The cpDNA haplotypes might represent ancient polymorphism rather than recent gene flow and expansion (Schaal et al 1998).…”
Section: Phylogeographic Analysismentioning
confidence: 99%
“…These studies indicated that in the East Asian temperate forests, phylogeographic patterns cannot be simply explained by southern glacial refugia (Qiu et al 2011). For example, Opgenoorth et al (2010) inferred that the Juniperus tibetica (Kom.) Kom.…”
mentioning
confidence: 99%